Usia Pertanggungjawaban Pidana Anak dalam Perspektif Neurolaw - Agustiawan, M. Hendri; Pujiyono, Pujiyono; Rozah, Umi (Jurnal Penegakan Hukum dan Keadilan, 2023)
Due to recent discoveries and technological advancements in neuroscience, we can gain a deeper understanding of the human brain that significantly impact juvenile criminal law, particularly concerning children's behavior and ability to regulate impulsive behavior. This study aims to analyze the current age of criminal responsibility in the Indonesian legal system using a neurolaw perspective that considers cognitive neuroscience and legal theory. The research utilizes normative legal research methodology with a statute approach and a neuroscience approach. The data obtained from literature research is then analyzed conceptually. The study results indicate that the age of criminal responsibility for children in Indonesia is 12 years; however, it has not yet reached 18 years. According to the neurolaw perspective, brain development within this age range is not fully matured and continues to undergo behavioral changes. This research implies the urgency of revising regulations regarding the age of criminal responsibility for children in Indonesia, considering the discoveries in neuroscience. Using a neurolaw perspective can encourage changes in legal policies that pay more attention to neurological factors in assessing juvenile criminal responsibility. As far as the law governs human behavior, the brain plays a crucial role in controlling that behavior. Therefore, a better understanding of the brain will lead to better and fairer laws.